2023
DOI: 10.1001/jamanetworkopen.2023.31011
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Neonatal Hypothermia in the Newborn Nursery and Associated Factors

Rebecca Dang,
Anisha I. Patel,
Yingjie Weng
et al.

Abstract: ImportanceThermoregulation is a key component of well-newborn care. There is limited epidemiologic data on hypothermia in late preterm and term infants admitted to the nursery. Expanding on these data is essential for advancing evidence-based care in a population that represents more than 3.5 million births per year in the US.ObjectiveTo examine the incidence and factors associated with hypothermia in otherwise healthy infants admitted to the newborn nursery following delivery.Design, Setting, and Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…Our prior manuscript on the epidemiology of hypothermia in the nursery found that both birth weight (BW) and GA were associated with hypothermia. 4 Therefore, in the current study, we performed a sensitivity analysis adding BW as a confounder to all models that adjusted for GA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our prior manuscript on the epidemiology of hypothermia in the nursery found that both birth weight (BW) and GA were associated with hypothermia. 4 Therefore, in the current study, we performed a sensitivity analysis adding BW as a confounder to all models that adjusted for GA.…”
Section: Discussionmentioning
confidence: 99%
“…2 "Moderate/Severe" hypothermia was defined as having an episode lasting ≥2 hours, at least episodes of hypothermia, and/or hypothermia <36.0˚C or lasting >2 hours 3 Column percentages may not add up to 100% due to rounding 4 Small-for-gestational age is defined as below the 10 th percentile using the Olsen intrauterine growth curves 48 5 Race, Ethnicity, and Language data are self-reported fields. "Unknown" is the default option and includes patients that decline to answer the question.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation